Pengaruh Indikator Makroekonomi, Harga Minyak Dunia Dan Indeks Bursa Asia Terhadap IHSG Periode 2015-2019 - Elvina Hartayu; R.A. Sista Paramita (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research aims to examine the effect of macroeconomic indicators (BI Rate, Inflation, and Gross Domestic Product), Crude Oil Prices, and Asian Stock Indexes (Nikkei 225 Index and Straits Times Index) on the Composite Stock Price Index (CSPI). This study uses monthly data with a total of 44 samples during The Fed Fund Rate's hike period from December 2015 to July 2019. Multiple linear regression is used for data analysis with IBM SPSS 23 software. The partial test result shows that the exchange rate has a negative influence on CSPI while BI Rate, Inflation, GDP, Crude Oil Prices, Nikkei 225 Index, and Straits Times Index do not influence CSPI movement. BI Rate doesn't affect because investors prefer stock returns over bank interest. Inflation doesn't affect because the increase in inflation is relatively low. GDP doesn't influence because the unequal income level makes people not interested in investing. The crude Oil price has no effect because the shares of oil and gas mining sub-sector companies are not attractive to investors. Nikkei 225 index doesn't influence because the economic situation between Japan and Indonesia is not related. The Straits Times Index doesn't influence because the number of domestic investors is more than foreign investors.